2012
DOI: 10.1021/ja211864w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Behavior of Metal–Organic Frameworks and Zeolites for Hydrocarbon Separations

Abstract: The objective of this work was to study the adsorption and separation of the most important families of hydrocarbon compounds on metal-organic frameworks (MOFs), in comparison with zeolites. For this purpose, we have selected four probe molecules, each of them representing one of these families, i.e., o- and p-xylene as aromatics, 1-octene as an alkene, and n-octane as an alkane. The separation of these four molecules was studied by binary breakthrough experiments. To represent the large diversity of MOF struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
207
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(218 citation statements)
references
References 68 publications
9
207
0
2
Order By: Relevance
“…23 Comparison of both the capacity and selectivity data confirms that NOTT-300 has potential for the separation of C 2 -alkyne/alkene, C 2 -alkene/alkane, C 2 /C 1 -hydrocarbon mixtures, which is relevent to the purification of ethylene, to olefin/paraffin separations, and natural gas upgrading, respectively. We therefore sought to understand these properties at the molecular level.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…23 Comparison of both the capacity and selectivity data confirms that NOTT-300 has potential for the separation of C 2 -alkyne/alkene, C 2 -alkene/alkane, C 2 /C 1 -hydrocarbon mixtures, which is relevent to the purification of ethylene, to olefin/paraffin separations, and natural gas upgrading, respectively. We therefore sought to understand these properties at the molecular level.…”
Section: Resultsmentioning
confidence: 72%
“…Comparison of INS spectra, measured at temperatures below 7(±0.1) K to minimise the thermal motion of the adsorbed hydrocarbons and the host, reveals five major changes in peak intensity on going from bare NOTT-300 to NOTT-300·3C 2 H 2 ( Figure 2d). Peaks I and II occur at low energy transfer (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) meV, respectively) and Peak III, IV, and V at high energy transfer (80, 95, 120 meV, respectively). Peaks I, III and IV can be assigned to translational, symmetric and asymmetric C-H vibrational motions of adsorbed C 2 H 2 molecules, respectively, based upon the INS spectra for condensed C 2 H 2 in the solid state.…”
Section: Resultsmentioning
confidence: 99%
“…Pure ZIF-8 membranes (209-212) fabricated on ceramic or polymer supports as well as ZIF-8-enabled mixed-matrix membranes (196,213,214); both show attractive productivity and selectivity for separating propylene/propane mixtures. While ZIF-8 demonstrates excellent diffusion selectivities for C 4 and heavier hydrocarbon mixtures, its diffusivity is usually unattractive for practical separation applications unless performed at elevated temperatures (199,200). IR microscopy was employed to study diffusion of CO 2 , CH 4 , C 2 H 4 , and C 2 H 6 in ZIF-8 by Caro and co-workers (204,205), and the results are in good consistency with the macroscopic method at low surface concentrations.…”
Section: Diffusion In a Prototypical Mofmentioning
confidence: 84%
“…Singlecrystal XRD determines window size of the six-membered ring to be 3.4Å (187). However, numerous experimental studies have suggested that the window is flexible, presumably due to rotation of the imidazole linkers, allowing adsorption of guest molecules significantly larger than 3.4Å (197)(198)(199)(200). It has been shown that molecules as large as 1,2,4-trimethylbenzene (d ß7.6Å) can diffuse into ZIF-8's β-cage, albeit slowly (201).…”
Section: Diffusion In a Prototypical Mofmentioning
confidence: 99%
“…More recently, porous metal-organic frameworks (MOFs) built up from inorganic sub-networks containing metal centers connected to polydentate organic linkers [9] have been found promising for the selective adsorption of diverse molecules [10][11][12][13][14][15][16]. This relatively new class of hybrid material is characterized by a high chemical and .…”
Section: Introductionmentioning
confidence: 99%